On sets of regular growth for functions analytic in an open half plane - Malyutin, K. G. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We introduce the notion of the set of regular growth for functions analytic in an open half plane. In particular, for a function of completely regular growth in an open half plane, the entire half plane is its set of regular growth. Developed theory is applied to the solution of a problem of Hermitian interpolation in a class of functions of completely regular growth in a half plane with given indicator.